Evaluation of nurse's performance in telemedicine - Claudinalle Farias Queiroz de Souza; Dulcineide Gonçalo de Oliveira; Alef Diogo da Silva Santana; Letícia Moura Mulatinho; Mirian Domingos Cardoso; Emanuela Batista Ferreira e Pereira; Jael Maria de Aquino
ABSTRACT Objective: Describe the nurse's role in the Telemedicine Program in Cardiology implanted in Pernambuco, Brazil. Methods: Qualitative study, with a target audience of nurses, performed between July and December 2016 at the Emergency Care Units. Data were collected through an online instrument, consisting of open and closed questions, performed with 19 professionals. The data were analyzed through the discourse of the collective subject by QuantiQualisoftware. Results: The sample consisted of 19 nurses, mostly female (80%), with a mean age of 30 years old. Two central ideas were constructed: nurses' knowledge about the Telemedicine Program in Cardiology; and actions developed by nurses. Also, a flow of the program's assistance was built. Final considerations: The nurse in Telecardiology performs functions of assistance and continuing education of monitoring and training for patients.